COVERS OF MUSIC AND SONGS WITHOUT NO LICENSE AGREEMENT OF THE CREATOR AND COPYRIGHT HOLDER CARRIED OUT BY CORPORATE AND INDIVIDUAL BLACK YOUTUBERS ON THE YOUTUBE CHANNEL - Edi Ribut Harwanto (Transpublika Publisher, 2022)
Criminal acts such piracy, copying, covering, distributing, and arranging musical works that belong to copyright holders, associated rights holders, and performers without a license or permission cannot be dealt with solely by illegal law enforcement under the Copyright Law. Furthermore, violators of piracy, song covers, music rearrangements without the consent of the copyright owners, associated rights, and performers shall face criminal penalties under Copyright Law No. 28 of 2014. This socio-legal research method study is a study that